Journey into America: The Challenge of Islam by Akbar Ahmed (Washington, DC: Brookings Institution Press, 2010. hbk. 528 pages) (American Journal of Islam and Society, 2011)
Akbar Ahmed’s latest book, Journey into America: The Challenge of Islam,has become one of the first comprehensive ethnographic studies of theMuslim community in America. Ahmed and his team of young researchersoffer a keen anthropological analysis of American Muslims that spans overseventy-five cities, one hundred mosques, and two thousand interviews.A modern-day version of Alexis de Tocqueville’s Democracy in America,Journey into America charts the various historical, social, and ideologicaltrajectories that have shaped both American and Muslim identities. Assuch, the work represents one of the first post-9/11 sociological commentariesthat attempt to define the nature of American Muslim identity and thepossibilities for its reevaluation. Over the course of nine chapters, Ahmedlays out for a general audience the groundwork for precisely such anendeavor ...